Manajemen Nyeri pada Pasien Kanker Payudara Stadium Paliatif dengan Cancer Pain - Mahmud; Sudadi; Ristianto, Muhammad Brian (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2022)
Pain is one of the most common and feared symptoms in patients with cancer, and even though good or complete pain control can be achieved in 80–90 % of cancer patients, cancer-related pain continues to be a major public health problem globally. Cancer pain becomes one of palliative care’s aspect. Palliative care is an approach that improves the quality of life of patients and their families facing the problem associated with life threatening illness. Palliative care needs early identification, examination, and therapy. There is screening for palliative care, such as 5-point palliative score. Cancer pain therapy uses step-ladder WHO guideline, with NRS or Numeric Rating Scale as its pain assessment. Breast cancer has the highest incidence in Indonesia, with bone metastatic becomes its most common occurrence in its late phase. Cancer pain management generally becomes important, particularly towards breast cancer and its bone metastatic manifestation..